Penataan Saluran dan Pemanfaatan Eco-Enzyme pada Limbah Ternak Babi di Kampung Sumodaran Banyuraden Gamping Sleman - YE. Suharno; Istiana Adianti (Jurnal Ilmiah Padma Sri Kreshna, 2024)
Pig farming is widely practiced by the community regarding livelihoods becauseeconomically the results are very profitable, and socially the community, especially ethnicChinese, utilizes pig livestock products in their various lives. Pig farming has increased asculinary tourism grows in various regions. As time goes by, poor pig waste managementbecomes a problem. This is the case occurs in Sumodaran Village, Banyuraden Sub-district,Gamping Sleman, which is 800 meters from the Integrated Campus of Widya MataramUniversity, and 3 km from the center of Yogyakarta City. In this area there is a pig farm that isquite troubling to the community because it discharges directly openly into the irrigationchannel behind the pen, causing water and air pollution to the surrounding environment. Pigwaste in the form of solid manure and water from the barn is left to flow into the irrigationchannel (the irrigation channel behind the barn is a tertiary channel of the Mataram sewer). Thislivestock waste without further handling causes water, air (unpleasant odor) and fly breedingso that it can pollute the surrounding environment. From the initial observations, the researcherwas encouraged to arrange the waste channel in a closed manner while utilizing eco-enzymesto break down feces or other waste so that there is no water and air pollution / odor. Keywords: pig manure, pollution, closed channel, eco-enzymes